-
\( \frac{3}{4}x + 3 - 2x = -\frac{1}{4} + \frac{1}{2}x + 5 \)
-
Combine like terms:
\( \frac{3}{4}x - 2x + 3 = -\frac{1}{4} + \frac{1}{2}x + 5 \) -
Rewrite \( -2x \) as \( -\frac{8}{4}x \):
\( \frac{3}{4}x - \frac{8}{4}x + 3 = -\frac{1}{4} + \frac{1}{2}x + 5 \) -
Combine \( \frac{3}{4}x - \frac{8}{4}x \):
\( -\frac{5}{4}x + 3 = -\frac{1}{4} + \frac{1}{2}x + 5 \) -
Combine constants on the right:
\( -\frac{5}{4}x + 3 = -\frac{1}{4} + 5 - \frac{1}{4} \)
\( -\frac{5}{4}x + 3 = \frac{19}{4} \) -
Move 3 to the right side:
\( -\frac{5}{4}x = \frac{19}{4} - 3 \)
\( -\frac{5}{4}x = \frac{19}{4} - \frac{12}{4} \)
\( -\frac{5}{4}x = \frac{7}{4} \) -
Multiply both sides by \(-\frac{4}{5}\):
\( x = -\frac{4}{5} * \frac{7}{4} \) -
Simplify:
\( x = -\frac{7}{5} \)
Final answer: \( x = -\frac{7}{5} \)